Predictors of multimorbidity among the Kurdish population living in the Northwest of Iran - N. Aminisani; L. Rastgou; S. M. Shamshirgaran; P. Sarbakhsh; S. Ghaderi; M. Hyde (BMC, 2020)
Abstract Background There is limited information about the predictors of multimorbidity (MM) among ethnic minority older adults in Iran. This study aimed to examine the impact of sociodemographic and lifestyle factors on the prevalence of MM, among older Kurdish people living in the Northwest of Iran. Methods The current study was conducted in Bukan city located in West Azarbaijan province in the Northwest of Iran. The data for this study was based on the enrolment phase of a longitudinal study on ageing among the Kurdish population aged 50-94 yearswhich was designed according to the elderly component of the PERSIAN Cohort in Iran. Stratified random sampling was used to select people aged 50 + from eight health centres in Bukan from Oct 2017 to Dec 2018. Those who accepted the invitation and completed the baseline questionnaire were included in this study (N = 1493; Response rate 75%). A range of different factors,including sociodemographic and lifestyle factors as well as self-reported chronic conditions, was obtained by trained interviewers. MM was defined as "coexistence of two or more chronic conditions in the same person". We included a list of 36 diseases/conditions in this analysis. Descriptive analysis and logistic regression were performed to compare the prevalence of MM according to different factors. Results Over a third of the participants (36.6%) had ≥2chronic conditionsand 15.7% had≥3 chronic conditions. Hypertension, diabetes, musculoskeletal conditions, fatty liver, and heart diseases were common chronic conditions. In a fully adjusted logistic regression model, older age (ORadj = 1.92, 95% CI: 1.48-2.48), being female (ORadj = 1.49, 95%CI: 1.14-1.94), living without aspouse (ORadj = 1.81, 95%CI: 1.34-2.44), and inadequate consumption of fruit and vegetables (ORadj = 1.33, 95%CI: 1.06-1.67) were associated with the higher prevalence of MM. Conclusion This study found that the prevalence of MM is relatively high among older Kurdishadults. Sociodemographic differences in the prevalence of MM might be of interest tothe health care system,and the prevalence of common chronic conditions in this study may highlight the need forlifestyle modifications in this community.